CLINICAL OUTCOMES OF SCLERAL BUCKLING COMBINED WITH PARS PLANA VITRECTOMY FOR RHEGMATOGENOUS RETINAL DETACHMENT - LUKANDY, ANDRY; Sumanti, Eugeni (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction and Objective: The various types of primary interventions for rhegmatogenous retinal detachment (RRD) include pars plana vitrectomy (PPV), scleral buckling (SB), and combination of both. Intraocular tamponade with silicone oil (SO) or expanding gas. This research was conducted to evaluate the clinical outcomes of SB combined with PPV as a treatment for RRD. Methods: This research was prospective descriptive study with total sampling for RRD treated by SB combined with PPV from August 2022 to January 2023 in RSUP. Prof. Dr. R.D. Kandou. BCVA, IOP, clinical findings, intraocular tamponade and complications after the surgery were observed. Results: Most of the patients was male with average age of 28 ± 40 years. RRD was observed in 6 eyes and laterality on right eye. BCVA was 2.5 ± 2 logMAR before the surgery and 2.3 ± 1 logMAR 1 month after the surgery. BCVA day 1, 1 week, 2 weeks and 1 month showed no significant difference after the surgery compared to baseline (p = 0.317, p = 0.949, p = 0.611, p= 0.611 respectively). Preoperative IOP was 7 ± 11 mmHg and 13.6 ± 10 mmHg 1 month after the surgery. IOP 1 week and 1 month showed significant difference (p = 0.027, p=0.011). IOP day 1, 2 weeks and 1 month showed there was no significant difference after the surgery on day 1 and 2 weeks. Conclusion: There were several clinical condition seen such as BCVA after the surgery didn’t improve as expected, subconjunctival bleeding was found the most as postoperative complications. Keyword: Scleral buckling, Pars plana vitrectomy, silicon oil, retinal detachment